Crosslinked hyaluronic acid gel with pore wall structure adaptive to tissue and cell growth

By adopting crosslinked hyaluronic acid gel with pore wall structure, the problem of gel dense structure in the prior art hindering metabolism is solved, and the cell growth and metabolism are supported after natural injection of the face, and the filling effect is maintained after metabolism is completed.

CN119931161APending Publication Date: 2025-05-06EYEBRIGHT MEDICAL TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510125029.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

The dense structure of existing crosslinked hyaluronic acid gels in the tissue hinders local metabolism, resulting in facial stiffness and unnatural expressions, and at the same time, the filling effect is lost after metabolism is completed, which has poor long-term effects.

Method used

A crosslinked hyaluronic acid gel with a pore wall structure is used, the median pore size of the pore wall structure is between 50-1000um, the particle size is suitable for the pore size, the swelling degree is between 20-200, the elastic modulus is between 100Pa and 1000Pa, and the pushing force is between 5N and 30N.

Benefits of technology

While maintaining the filling effect, the gel supports cell adhesion, growth and differentiation phenotype, supports the delivery of nutrients and metabolites, and the face is natural after injection, and can maintain a certain correction effect after metabolism is completed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119931161A_ABST
    Figure CN119931161A_ABST
Patent Text Reader

Abstract

The invention relates to a cross-linked hyaluronic acid gel having a pore wall structure adapted to tissue and cell growth and particles thereof. The invention further relates to a preparation method of the cross-linked hyaluronic acid gel, a composition containing the cross-linked hyaluronic acid gel and application of the cross-linked hyaluronic acid gel.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with an application date of July 28, 2022, application number 202210897934.4, and invention name “Cross-linked hyaluronic acid gel with a pore wall structure suitable for tissue and cell growth”. Technical Field

[0002] The present invention relates to the field of medical biomaterials, in particular to cross-linked hyaluronic acid gel and its particles. The present invention also relates to a preparation method of the cross-linked hyaluronic acid gel of the present invention, a composition comprising the cross-linked hyaluronic acid gel of the present invention, and its use. Background Art

[0003] Hyaluronic acid is an important component of human skin, cartilage tissue and joint lubricating fluid. It is a chain polymer composed of repeated connections of disaccharide units of (1-β-4) D-glucuronic acid and (1-β-3) N-acetylglucosamine. Thanks to its high water retention, lubricity and no species difference, natural hyaluronic acid is widely used in medical filling and beauty, osteoarthritis treatment and eye surgery.

[0004] Natural hyaluronic acid has the disadvantages of short half-life in tissues and easy degradation and diffusion, which greatly limits its application in the fields of medical cosmetic filling. The common method of solving the above problems of natural hyaluronic acid is to cross-link and modify natural hyaluronic acid with a chemical cross-linking agent and then granulate it into injectable gel particles. The chemical cross-linking repair is to improve the product's anti-degradation property, and the granulation is to allow the gel to be pushed out of the injection needle into the skin. For example, CN107223061 discloses a sterile composition, which contains cross-linked hyaluronic acid cross-linked with 1,4-butanediol diglycidyl ether, which can be used for sculpting, filling or correction of the chin area, mandibular shape or nose. For example, CN104072814 discloses a composition for preparing cross-linked hyaluronic acid, which contains a hyaluronic acid alkaline aqueous solution with a concentration of 15-25wt% and a cross-linking agent, and the composition has a Tanδ value of 0.5-1.5 at a frequency of 0.02-1Hz. For example, CN1950039 discloses an injectable gel particle with a particle size of 1 to 5 mm based on glucosaminoglycan, the preparation method of which includes preparing a gel composed of a viscoelastic medium at a desired concentration, and physically breaking the gel, such as chopping, mashing or passing the gel through a filter with an appropriate pore size. The particle can be used for soft tissue augmentation implants.

[0005] Thanks to its non-immunogenicity, strong volume support capacity, and reversible filling process, cross-linked hyaluronic acid gel is considered by many to be one of the most ideal skin fillers. However, from the perspective of tissue engineering, a good tissue filler should not affect or support cell adhesion, growth and differentiation phenotypes while providing sufficient mechanical support, and should not affect or support the delivery of nutrients and metabolites. However, cross-linked hyaluronic acid gel is a water-rich cross-linked network structure formed by cross-linking of polymer solutions. Under conventional preparation methods (such as CN107223061 and CN104072814 mentioned above), since cross-linking occurs at the molecular structure level of the uniform solution, the cross-linked network formed has a three-dimensional structure in space but a very small pore size. When this dense cross-linked gel particle is injected into the tissue, an inert physical barrier is also formed while the volume is filled, which hinders the metabolic activity of the local tissue, and easily leads to facial stiffness and unnatural expression. If this problem is to be circumvented by reducing the particle size of the gel particles, it often leads to the lack of sufficient support capacity of the gel, and the expected tissue filling effect cannot be achieved.

[0006] In summary, conventional cross-linked hyaluronic acid gel can only achieve inert filling and volume expansion of tissues, but cannot support the metabolism of local tissues. It is also easy to cause facial stiffness and unnatural expressions. After the metabolism is completed, it often loses all the filling effects, and the long-term effect is poor. Therefore, there is an urgent need for a cross-linked hyaluronic acid gel that is compatible with tissue and cell growth, which can maintain the filling effect while supporting cell adhesion, growth and differentiation phenotypes, supporting the delivery of nutrients and metabolites, making the face natural after injection, and supporting long-term skin volume regeneration and repair. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a cross-linked hyaluronic acid gel with a pore wall structure, which is used for medical filling and beauty. The filling site is preferably a site where local tissues need metabolism and need to provide sufficient support, including the human body, such as the nasolabial grooves, chin, mandibular shape, cheeks, zygomatic arches, eye circles, brows, nose bridge, and nose bridge in humans.

[0008] The gel described in the present invention overcomes the shortcomings of known cross-linked hyaluronic acid. The gel has pore wall structure characteristics that are compatible with tissue cell growth. While maintaining a filling effect, it can also support cell adhesion, growth and differentiation phenotypes, and support the transport of nutrients and metabolites. The face looks natural after injection, and after metabolism is completed, a certain correction effect can be maintained due to the regeneration of autologous tissues and cells.

[0009] According to one embodiment of the present invention, the median pore size of the pore wall structure is between 50-1000um, preferably 80-500um, more preferably 90-300um, or even 100-200um; the pore size of the gel of the present invention is a characteristic value reflecting the pore wall structure of the gel, which is defined as the distance between the two farthest points of the pore. The pore size of the gel can be measured using conventional methods, such as by quantifying according to the following method: the clot is immersed in ethanol aqueous solutions with concentrations of 30, 50, 70, 90, and 100% for 20 minutes in sequence to achieve gradient dehydration, and then vacuum dried after immersion in silazane for 10 minutes. The dried sample is characterized by SEM, and 4 500×500μm squares are randomly selected in the field of view, and 20 pore sizes are randomly measured and statistically analyzed to obtain the median pore size.

[0010] According to another embodiment of the present invention, the median particle size D of the gel particles is 50 The particle size of the gel particles of the present invention is between 50-1000um, preferably 100-800um, more preferably 300-700um, or even 400-600um. The particle size of the gel particles of the present invention is a characteristic value reflecting the size of the gel particles, which can be measured in a 0.9% sodium chloride aqueous solution using a laser particle size analyzer equipped with a wet disperser.

[0011] According to another embodiment of the present invention, there is an adaptive relationship between the particle size and pore size of the gel, and the ratio of the median pore size of the pore wall structure to the median particle size of the gel particles is between 0.05-1, preferably 0.1-0.8, more preferably 0.1-0.6, or even 0.15-0.5.

[0012] According to another embodiment of the present invention, the swelling degree of the gel is between 20-200, preferably 40-150, and more preferably 40-100. The swelling degree is an important parameter for the crosslinking degree of the reaction gel. Under the same conditions, the greater the crosslinking degree of the gel, the smaller the swelling degree. The swelling degree can be measured using conventional methods, such as quantified by the following method: the ratio of the weight of the gel immersed in a 0.9% sodium chloride solution for one hour to its weight after complete drying.

[0013] According to another embodiment of the present invention, without wishing to be bound by any theory, the applicant has found that, under the premise that the pore size of the gel is compatible with the growth of tissues and cells, the larger the particle size of the gel or the lower the swelling degree, the better the stability of the gel pore wall structure, the larger the elastic modulus, and the better the plastic effect. However, the higher the difficulty of push injection, the greater the push-out force, the more difficult it is to inject subcutaneously, and the more difficult it is to perform precise operations; the smaller the particle size of the gel particles or the higher the swelling degree, the worse the stability of the gel pore wall structure, the lower the gel push-out force, but the lower the elastic modulus, the easier it is to collapse, and the supporting performance and maintenance time decrease. The applicant was surprised to find that, under the conditions that meet the following formula, the gel particles described in the present invention have a pore size that is compatible with the growth of tissues and cells, and can also have better volume filling performance and appropriate push-out force:

[0014] 50≤swelling degree / (median pore size / median particle size)≤600.

[0015] According to another embodiment of the present invention, the elastic modulus of the gel at 1 Hz is 100 Pa to 1000 Pa, preferably 200 Pa to 500 Pa. The elastic modulus can be measured using conventional methods, such as using a TA DHR rotational rheometer, using a plate diameter of 40 mm at a gap height of 1 mm, and measured at a constant temperature of 25° C. Each measurement is performed at a strain of 0.8% and a frequency of 1 Hz.

[0016] According to another specific embodiment, the push-out force of the cross-linked hyaluronic acid gel is between 5N and 30N, more preferably between 5N and 20N. Without wishing to be bound by any theory, the applicant has found that the push-out force of the gel of the present invention is a characteristic value reflecting the injectability of the gel, which can be measured using conventional methods, such as quantified using the following method: 1 ml of gel sample is loaded into a cylinder with a length of 80mm and an inner diameter of 6.4mm, and a 27G injection needle is connected to the front section of the cylinder. When the gel is pushed out of the injection needle at an extrusion rate of 30mm / min, the average value of the force required is recorded as the push-out force.

[0017] According to another embodiment of the present invention, the cross-linked hyaluronic acid gel generally comprises a gel containing hyaluronic acid (HA) cross-linked with a cross-linking agent selected from the following, wherein the cross-linking agent is selected from glycidyl ether, diepoxide, biscarbodiimide, divinyl sulfone, multifunctional polyethylene glycol-based cross-linking agent, etc. The cross-linking agent is, for example, but not limited to, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutylene glycol diglycidyl ether, 1,2-bis(2,3-epoxypropoxy)-2,3-ethylene, 1,2,7,8-diepoxyoctane, oxalylhydrazide, hexamethylenediamine, divinyl sulfone or a combination thereof.

[0018] According to another embodiment of the present invention, the cross-linked hyaluronic acid gel, wherein the molecular weight of HA used for cross-linking is between 100,000 and 5,000,000, can also be a composition of different molecular weights, preferably between 500,000 and 4,000,000, more preferably between 500,000 and 2,000,000.

[0019] According to another specific embodiment, the HA concentration of the gel is greater than 16 mg / ml, preferably 20-25 mg / ml, and more preferably 21-23 mg / ml.

[0020] According to another specific embodiment, the cross-linking degree of the gel is between 2-10%, preferably 4-8%, and more preferably 5-7%.

[0021] According to another specific embodiment, the cross-linked hyaluronic acid gel according to the present invention may also have at least one of the following:

[0022] - the protein content of the cross-linked hyaluronic acid gel is not more than 0.1% by mass;

[0023] - the heavy metal content of the cross-linked hyaluronic acid gel is no more than 5 μg / g;

[0024] - the cross-linking agent residue in the cross-linked hyaluronic acid gel is no more than 2 μg / g; and / or

[0025] -The bacterial endotoxin content of the cross-linked hyaluronic acid gel is no more than 0.5EU / mL.

[0026] The cross-linked hyaluronic acid gel of the present invention has the above-mentioned pore wall structure characteristics, and can be obtained by the preparation method of the cross-linked hyaluronic acid gel provided by the present invention.

[0027] The present invention also relates to a method for preparing a cross-linked hyaluronic acid gel, comprising (1) a dissolving step: uniformly dissolving hyaluronic acid, its metal salt, its derivative or a mixture thereof in water.

[0028] According to another specific embodiment, the preparation method includes (2) a dispersion step: adding an alcohol substance to the solution obtained in the dissolution step and stirring the mixture to form a mixed solution.

[0029] According to another specific embodiment, the preparation method comprises the following steps:

[0030] (1) Dissolving step: uniformly dissolving hyaluronic acid, its metal salt, its derivative or a mixture thereof in water;

[0031] (2) Dispersion step: adding an alcohol substance to the above solution and stirring to form a mixed solution;

[0032] (3) adding a cross-linking agent to the mixed solution and adjusting the pH to non-neutral;

[0033] (4) The mixed solution is cooled to between -10 and -50°C and a cross-linking reaction is performed.

[0034] (5) After the reaction is completed, neutralization, purification and homogenization are optionally performed.

[0035] According to another embodiment of the present invention, the hyaluronic acid metal salt refers to a salt formed by hyaluronic acid and metal ions, such as but not limited to sodium salt, potassium salt, magnesium salt, calcium salt, zinc salt of hyaluronic acid and combinations thereof.

[0036] According to another embodiment of the present invention, the hyaluronic acid derivative refers to a polysaccharide containing a hydroxyl group, such as but not limited to carboxymethyl cellulose, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan or guar gum, and a mixture thereof.

[0037] According to another embodiment of the present invention, the alcohol substance refers to a compound containing a hydroxyl group bonded to a carbon on a hydrocarbon group or a benzene ring side chain in the molecule, preferably an alcohol substance miscible with water, and the alcohol substance is selected from monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1-26 carbon atoms, in particular monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1-16 carbon atoms, or even monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1-8 carbon atoms, including but not limited to methanol, ethanol, benzyl alcohol, ethylene glycol, etc.

[0038] According to another embodiment of the present invention, the crosslinking agent is selected from glycidyl ether, diepoxide, biscarbodiimide, divinyl sulfone, multifunctional polyethylene glycol-based crosslinking agent and mixtures thereof. The crosslinking agent is, for example but not limited to, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutylene glycol diglycidyl ether, 1,2-bis(2,3-epoxypropoxy)-2,3-ethylene, 1,2,7,8-diepoxyoctane, oxalylhydrazide, hexamethylenediamine, divinyl sulfone, and mixtures thereof.

[0039] According to another embodiment of the present invention, the concentration of hyaluronic acid, its metal salts, its derivatives or mixtures thereof is at least 0.05% w / v and not higher than 50% w / v, preferably 0.1-30% w / v, even 0.5-10% w / v, particularly 2-8% w / v, especially 4%-6% w / v.

[0040] According to another embodiment of the present invention, the concentration of the alcohol substance is at least 0.05% v / v and not higher than 50% v / v, preferably 0.1-30% v / v, even 0.5-10% v / v, particularly 2-8% v / v, especially 4%-6% v / v.

[0041] According to another embodiment of the present invention, the concentration of the crosslinking agent is 0.05-20% w / w, preferably 0.5-10% w / w, more preferably 1-8% w / w, more preferably 2%-6% w / w.

[0042] According to another embodiment of the present invention, in the cross-linked hyaluronic acid gel, the mass ratio of the cross-linking agent to the hyaluronic acid in step (3) is 0.05-20% w / w, preferably 0.5-10% w / w, more preferably 1-8% w / w, more preferably 2%-6% w / w.

[0043] According to another embodiment of the present invention, the non-neutral environment can be an acidic environment with a pH value of 1-6, preferably 1-4, or an alkaline environment with a pH value of 9-14, preferably 11-14.

[0044] According to another embodiment of the present invention, in the cross-linked hyaluronic acid gel, the cross-linking reaction time in step (4) is within 100 days, preferably 1 to 28 days, more preferably 3 to 21 days, and more preferably 5 to 14 days.

[0045] According to another embodiment of the present invention, for the cross-linked hyaluronic acid gel, the neutralization in step (5) refers to neutralizing the non-neutral environment in the cross-linking reaction to a neutral environment, for example, a pH of about 7, such as a pH of 6.5 to 7.5, particularly 6.8 to 7.2, and especially 6.9 to 7.1.

[0046] According to another embodiment of the present invention, the purification in step (5) of the cross-linked hyaluronic acid gel refers to reducing the amount of unreacted cross-linking agent residue in the gel to less than 2 μg / g, for example but not limited to, dialyzing the gel in a pH-neutral phosphate buffer until the amount of cross-linking agent residue is less than 2 μg / g.

[0047] According to another embodiment of the present invention, for the cross-linked hyaluronic acid gel, the homogenization in step (5) refers to uniformly dispersing the cross-linked hyaluronic acid obtained in the cross-linking reaction into particles or solutions by means of, for example but not limited to, grinding, crushing, and cutting.

[0048] The present invention also relates to the application of cross-linked hyaluronic acid gel in medical cosmetology, such as but not limited to the treatment of facial fine lines, facial sculpting, and correction of facial features.

[0049] According to another embodiment of the present invention, the cross-linked hyaluronic acid gel is used in surgical operations, soft tissue filling, wound hemostasis, wound healing, anti-scarring, scar repair, joint lubrication, and joint protection.

[0050] The present invention also relates to the use of the cross-linked hyaluronic acid gel of the present invention, the composition containing the cross-linked hyaluronic acid gel of the present invention, or the medical device containing the cross-linked hyaluronic acid gel of the present invention in medical cosmetology, such as the treatment of facial fine lines, facial sculpture, correction of facial features, surgical operations or surgical treatments such as adhesion prevention and scar prevention, especially in soft tissue filling, wound hemostasis, wound healing, scar prevention, scar repair, joint lubrication, and joint protection.

[0051] According to a specific embodiment of the present invention, the cross-linked hyaluronic acid gel of the present invention is used in the dermis and subcutaneous layer.

[0052] The gel described in the present invention overcomes the shortcomings of known cross-linked hyaluronic acid. The gel has pore wall structure characteristics that are compatible with tissue cell growth. While maintaining a filling effect, it can also support cell adhesion, growth and differentiation phenotypes, and support the transport of nutrients and metabolites. The face looks natural after injection, and after metabolism is completed, a certain correction effect can be maintained due to the regeneration of autologous tissues and cells.

[0053] The cross-linked hyaluronic acid gel of the present invention has a particle size that is compatible with the pore size and also has a suitable injection force and excellent volume filling performance.

[0054] This application also includes the following technical solutions and their combinations:

[0055] 1. Cross-linked hyaluronic acid gel particles, wherein the gel particles have a porous structure, and the median pore size is between 50-1000um, preferably 80-500um, more preferably 90-300um, or even 100-200um.

[0056] 2. The cross-linked hyaluronic acid gel particles according to item 1, wherein the median particle size D of the gel particles is 50 Between 50-1000um, preferably 100-800um, more preferably 300-700um, even 400-600um.

[0057] 3. The cross-linked hyaluronic acid gel particles according to any one of the preceding items, wherein the median of the pore size of the gel particles is equal to the median of the particle size of the gel particles D 50 The ratio is between 0.05-1, preferably 0.1-0.8, more preferably 0.1-0.6, or even 0.15-0.5.

[0058] 4. The cross-linked hyaluronic acid gel particles according to any of the preceding items, wherein the swelling degree of the gel particles is between 20-200, preferably 40-150, and more preferably 40-100.

[0059] 5. The cross-linked hyaluronic acid gel particle according to any one of the preceding items, wherein the cross-linked hyaluronic acid gel particle is made to conform to the following formula:

[0060] 50≤swelling degree / (median pore size / median particle size)≤600.

[0061] 6. The cross-linked hyaluronic acid gel particles according to any one of the preceding items, wherein the elastic modulus of the gel particles is 100 Pa to 1000 Pa, preferably 200 Pa to 500 Pa at 1 Hz.

[0062] 7. The cross-linked hyaluronic acid gel particles according to any of the preceding items, wherein the pushing force of the gel is between 5N and 30N, more preferably between 5N and 20N, or even between 10-15N.

[0063] 8. The cross-linked hyaluronic acid gel particle according to any of the preceding items, wherein the gel particle comprises a gel containing hyaluronic acid (HA) cross-linked with a cross-linking agent selected from the group consisting of glycidyl ethers, diepoxides, biscarbodiimides, divinyl sulfones, multifunctional polyethylene glycol-based cross-linking agents, etc. The cross-linking agent is, for example, but not limited to, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutylene glycol diglycidyl ether, 1,2-bis(2,3-epoxypropoxy)-2,3-ethylene, 1,2,7,8-diepoxyoctane, oxalylhydrazide, hexamethylenediamine, divinyl sulfone, or a combination thereof.

[0064] 9. The cross-linked hyaluronic acid gel particles according to any of the preceding items, wherein the HA concentration in the gel particles is greater than 16 mg / ml, preferably 20-25 mg / ml, and more preferably 21-23 mg / ml.

[0065] 10. The cross-linked hyaluronic acid gel particles according to any of the preceding items, wherein the degree of cross-linking is between 2-10%, preferably 4-8%, and more preferably 5-7%.

[0066] 11. The cross-linked hyaluronic acid gel particle according to any one of the preceding items, which has at least one of the following:

[0067] - the gel comprises cross-linked hyaluronic acid (HA) cross-linked with 1,4-butanediol diglycidyl ether (BDDE);

[0068] - the protein content of the cross-linked hyaluronic acid gel is not more than 0.1% by mass;

[0069] - the heavy metal content of the cross-linked hyaluronic acid gel is no more than 5 μg / g;

[0070] - the cross-linking agent residue in the cross-linked hyaluronic acid gel is no more than 2 μg / g; and / or

[0071] -The bacterial endotoxin content of the cross-linked hyaluronic acid gel is no more than 0.5EU / mL.

[0072] 12. A method for preparing cross-linked hyaluronic acid gel particles, in particular cross-linked hyaluronic acid gel particles according to any of the preceding items, comprising the following steps:

[0073] (1) Dissolving step: dissolving hyaluronic acid, its metal salt, its derivative or a mixture thereof to form a solution;

[0074] (2) Dispersion step: adding an alcohol substance to the above solution to form a dispersed mixed solution.

[0075] 13. The method according to item 12, comprising the following steps:

[0076] (1) Dissolution step: Dissolve hyaluronic acid, its metal salt, its derivative or a mixture thereof in water to form a solution.

[0077] 14. The method according to item 12, comprising the following steps:

[0078] (1) Dissolving step: uniformly dissolving hyaluronic acid, its metal salt, its derivative or a mixture thereof in water to form a solution;

[0079] (2) Dispersion step: adding an alcohol substance to the above solution and stirring to form a dispersed mixed solution;

[0080] (3) adding a cross-linking agent to the mixed solution and adjusting the pH to non-neutral;

[0081] (4) The mixed solution is cooled to between -10 and -50°C and a cross-linking reaction is performed.

[0082] (5) After the reaction is completed, neutralization, purification and homogenization are optionally performed.

[0083] 15. The method according to item 12 above, wherein the alcohol substance is selected from monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1 to 26 carbon atoms, in particular monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1 to 16 carbon atoms, or even monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1 to 8 carbon atoms, such as methanol, ethanol, benzyl alcohol, ethylene glycol.

[0084] 16. Use of the cross-linked hyaluronic acid gel particles according to any one of items 1 to 11 above in the preparation of products for medical cosmetics such as treatment of facial fine lines, facial sculpting, correction of facial features, surgical operations or surgical treatments such as anti-adhesion and anti-scarring.

[0085] 17. Use of the cross-linked hyaluronic acid gel particles according to any one of items 1 to 11 above in the preparation of products for soft tissue filling, wound hemostasis, wound healing, anti-scar, scar repair, joint lubrication, and joint protection.

[0086] 18. Use of the cross-linked hyaluronic acid gel particles according to any one of items 1 to 11 in the dermis and subcutaneous tissue. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] Figure 1 The staining effect of the gel of the present invention after being injected into the tissue in Example 3 is illustrated.

[0088] Figure 2 The staining effect of the existing technology gel after being injected into the tissue in Comparative Example 3.1 is illustrated.

[0089] Figure 3 The staining effect of another prior art gel after being injected into the tissue in Comparative Example 3.2 is illustrated. DETAILED DESCRIPTION

[0090] In order to better understand the present invention, it is further described below in conjunction with specific embodiments.

[0091] The hyaluronic acid concentration described in the present invention refers to the mass ratio of hyaluronic acid to the volume ratio of water (w / v%).

[0092] The sodium hydroxide concentration described in the present invention refers to the mass ratio of sodium hydroxide to the volume ratio of water (w / v%).

[0093] The concentration of 1,4-butanediol diglycidyl ether (BDDE) described in the present invention refers to the mass ratio of BDDE to hyaluronic acid (w / w%).

[0094] Embodiment 1:

[0095] This example investigates the pore wall structure pore size and gel particle size of the obtained gel under different reaction conditions under the process method described in the present invention. Hyaluronic acid is uniformly dissolved in water, and then a certain concentration of ethanol is added and stirred evenly. A certain concentration of BDDE is added to the mixed solution, and then sodium hydroxide is added until its concentration reaches 1% (w / v). The mixed solution is cooled to a specified temperature and a cross-linking reaction is carried out. After the reaction is completed, the pH is adjusted to neutral with a hydrochloric acid solution, and the cross-linked sodium hyaluronate gel is obtained after being dialyzed and purified in a PBS buffer and mechanically homogenized, and a concentration of 20 mg / ml is obtained. The test method for gel performance is as follows.

[0096] The pore size of the gel pore wall structure was measured as follows: the clot was immersed in 30, 50, 70, 90, and 100% ethanol aqueous solutions for 20 minutes in sequence to achieve gradient dehydration, and then immersed in silazane for 10 minutes and then vacuum dried. The dried sample was characterized by SEM, and 4 500×500μm squares were randomly selected in the field of view, and 20 pore sizes were randomly measured and statistically analyzed to obtain the median pore size.

[0097] The median gel particle size is measured in a 0.9% sodium chloride aqueous solution using a laser particle size analyzer equipped with a wet dispersion instrument.

[0098] The swelling of the gel was measured by immersing the gel in a 0.9% sodium chloride solution for one hour and comparing its weight with its weight after complete drying.

[0099] The gel elastic modulus was measured using a TA DHR rotational rheometer with a plate diameter of 40 mm at a gap height of 1 mm and a constant temperature of 25° C. Each measurement was performed at a strain of 0.8% and a frequency of 1 Hz.

[0100] The push-out force of the gel was determined as follows: 1 ml of the gel sample was placed in a cylinder 80 mm long and 6.4 mm in inner diameter, with a 27G injection needle connected to the front of the cylinder. The average force required to push the gel out of the injection needle at an extrusion rate of 30 mm / min was recorded as the push-out force.

[0101] The results showed that a cross-linked sodium hyaluronate gel with a pore wall structure was formed under these conditions.

[0102] Comparative Example 1: In this comparative example, a gel was prepared under the same sodium hyaluronate concentration, crosslinking agent dosage and alkaline conditions as in Example 1, under conventional process conditions of a crosslinking reaction temperature of 40°C and a crosslinking reaction time of 4h. The preparation method is as follows, wherein the sodium hyaluronate concentration is 5w / v%, the crosslinking reaction temperature is 40°C, and the crosslinking reaction time is 4h.

[0103] A certain concentration of hyaluronic acid is uniformly dissolved in water, a certain concentration of BDDE is added to the mixed solution, and then sodium hydroxide is added until its concentration reaches 1% (w / v). The temperature of the mixed solution is raised to a specified temperature and a cross-linking reaction is performed. After the reaction is completed, the pH is adjusted to neutral with a hydrochloric acid solution, and the mixture is placed in a PBS buffer for dialyzed purification and mechanically homogenized to obtain a cross-linked sodium hyaluronate gel with a concentration of 20 mg / ml. The test method for the gel performance is the same as in Example 1.

[0104] The results showed that a cross-linked sodium hyaluronate gel could be formed under the conditions of the comparative example, but its pore wall structure was not obvious and could not meet the needs of local tissue metabolism.

[0105] Table 1 Pore diameter of gel obtained under the preparation process conditions of Example 1

[0106]

[0107] Embodiment 2:

[0108] This example examines whether the gel obtained in Example 1 conforms to the following formula, as well as its supporting capacity and ease of push-out.

[0109] 50≤swelling degree / (median pore size / median particle size)≤600

[0110] The test method of gel performance is the same as that in Example 1.

[0111]

[0112] The results showed that the elastic modulus of the gel under the three conditions was high and the push-out force was within the applicable range, meeting the needs of clinical injection and being applicable in the treatment of facial fine lines, facial sculpting, and correction of facial features.

[0113] Comparative Example 2:

[0114] This comparative example investigates the supporting capacity and ease of push-out of the gel of the present invention when the following formula is not met.

[0115] 50≤swelling degree / (median pore size / median particle size)≤600

[0116] The test method of gel performance is the same as that in Example 1.

[0117]

[0118] The results show that under the two conditions, the gel performance or the push-out force is too high, or the support performance is too low, which cannot meet the application requirements in the treatment of facial fine lines, facial sculpting, and correction of facial features. The results show that under the product parameter conditions shown in Comparative Example 2.1, the swelling degree / (median pore size / median particle size) exceeds 600, and the product has a high support capacity, but the push-out force is too large, and the ease of push-out is poor, which cannot meet the needs of clinical injection. Under the product parameter conditions shown in Comparative Example 2.2, the swelling degree / (median pore size / median particle size) is less than 50. At this time, the structural stability of the product gel particles is greatly reduced, the elastic modulus is low, and it does not have sufficient support performance. In summary, the above two comparative examples cannot meet the application requirements in the treatment of facial fine lines, facial sculpting, and correction of facial features.

[0119] Embodiment 3:

[0120] In order to better illustrate that the gel of the present invention has pore wall structural characteristics that are compatible with tissue and cell growth, can support the migration and growth of tissues and cells, and support the transportation of signal molecules, nutrients and metabolites, an intradermal implantation experiment was conducted using Example 1.1 as the subject.

[0121] A four-week-old male New Zealand rabbit was taken. After the back skin was prepared and disinfected, 0.05 ml of the cross-linked hyaluronic acid gel of the present invention was injected into the back skin of the New Zealand rabbit to mark the location of the skin papule. After 13 weeks of implantation, the skin papule and the surrounding 0.5 cm normal skin tissue were removed along the mark. When taking the sample, avoid compression of the skin papule, and immediately put the removed skin tissue into a 50 ml centrifuge tube filled with 10% neutral formalin. After the tissue fixation was completed, it was dehydrated, transparent, sliced, and stained with hematoxylin and eosin.

[0122] After sealing, the slides were imaged under a tissue section pathology scanner. The tissue staining results are shown in the attached figure. Figure 1 The results showed that the gel still showed obvious pore wall structural characteristics 13 weeks after implantation. There was no obvious boundary between the cells and the gel, and the cells were distributed evenly, proving that the gel can support the migration and growth of tissues and cells, and support the transport of signal molecules, nutrients and metabolites.

[0123] Comparative Example 3.1

[0124] In this comparative example, a long-term intradermal implantation experiment was conducted using the commercially available product Restylane 2 (sold by Q-Med AB as Modified Sodium Hyaluronate Gel for Injection). The experimental steps were the same as those in Example 3. The gel of this product has the characteristics of large particle size and no obvious pore wall structure. The tissue staining results are shown in the attached figure. Figure 2 As shown in the figure, the gel exists in the form of an inert physical barrier in the tissue. The cells are mainly distributed in the gaps between the gel and cannot penetrate the gel. There is a clear dividing line between the cells and the gel, and the distribution is extremely uneven. This proves that the gel forms an inert physical barrier locally, hindering the metabolic activity of the local tissue.

[0125] Comparative Example 3.2

[0126] This comparative example used the commercially available product Juvederm ULTRA (sold by Allergan Information Consulting (Shanghai) Co., Ltd. as "Juvederm ULTRA / cross-linked sodium hyaluronate gel for injection") for a long-term intradermal implantation experiment. The experimental steps were the same as those in Example 3. The tissue staining results are shown in the attached figure. Figure 3As shown. The gel of this product has the characteristic of a wide distribution of particle sizes. There are particles of various sizes in the gel at the same time, and there is no obvious pore wall structure. From the histological sections, it can be seen that the gel exists in the tissue as an inert physical barrier. In the local area where the gel particles are small, the metabolism of the tissue is not significantly affected, and the cell distribution is relatively uniform. However, near the large particle gel that mainly plays a supporting role, the cell distribution is also relatively uneven, and can only grow around the edge of the gel. This proves that the large particle component in the gel still forms an inert physical barrier locally, hindering the metabolic activity of the local tissue.

[0127] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited by the embodiments. Any other changes, modifications, combinations, substitutions and simplifications made without departing from the spirit and principles of the present invention shall be considered as equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. Cross-linked hyaluronic acid gel particles, wherein the gel particles have a porous structure, wherein the cross-linked hyaluronic acid gel particles conform to the following formula: 50≤swelling degree / (median pore size / median particle size)≤600, The median pore size of the gel particles is between 80-200 μm. The median particle size of the gel particles is D 50 300-700um, The swelling degree of the gel particles is 20-150. The pushing force of the gel is between 10N and 30N. wherein the elastic modulus of the gel particles is 100 Pa to 500 Pa at 1 Hz, The median of the pore size of the gel particles is equal to the median of the particle size of the gel particles D 50 The ratio is between 0.1-0.

5.

2. The cross-linked hyaluronic acid gel particles according to claim 1, wherein the gel particles comprise a gel containing hyaluronic acid (HA) cross-linked with a cross-linking agent selected from the group consisting of glycidyl ether, diepoxide, biscarbodiimide, divinyl sulfone, and a multifunctional polyethylene glycol-based cross-linking agent.

3. The cross-linked hyaluronic acid gel particles according to claim 1 or 2, wherein the gel particles comprise a gel containing hyaluronic acid (HA) cross-linked with a cross-linking agent selected from the following: 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutylene glycol diglycidyl ether, 1,2-bis(2,3-epoxypropoxy)-2,3-ethylene, 1,2,7,8-diepoxyoctane, oxalyl dihydrazide, hexamethylenediamine, divinyl sulfone or a combination thereof.

4. The cross-linked hyaluronic acid gel particles according to claim 1 or 2, which have at least one of the following: - the HA concentration in the gel particles is greater than 16 mg / ml, in particular 20-25 mg / ml, even 21-23 mg / ml; - the degree of crosslinking of the gel particles is between 2 and 10%, in particular 4 to 8%, or even 5 to 7%; - the gel comprises cross-linked hyaluronic acid (HA) cross-linked with 1,4-butanediol diglycidyl ether (BDDE); - the protein content of the cross-linked hyaluronic acid gel is not more than 0.1% by mass; - the heavy metal content of the cross-linked hyaluronic acid gel is no more than 5 μg / g; - the cross-linking agent residue in the cross-linked hyaluronic acid gel is no more than 2 μg / g; and / or -The bacterial endotoxin content of the cross-linked hyaluronic acid gel is no more than 0.5EU / mL.

5. The cross-linked hyaluronic acid gel particles according to claim 1 or 2, wherein the median particle size D of the gel particles is 50 is 400-600um; or, the median of the pore size of the gel particles is equal to the median of the particle size of the gel particles D 50 The ratio is 0.15-0.5; or, the swelling degree of the gel particles is 40-100; or, the elastic modulus of the gel particles is 200Pa to 500Pa at 1Hz.

6. The cross-linked hyaluronic acid gel particles according to claim 1 or 2, wherein the pushing force of the gel is between 10N and 20N, in particular between 10-15N.

7. A method for preparing the cross-linked hyaluronic acid gel particles according to any one of claims 1 to 6, comprising the following steps: (1) Dissolving step: uniformly dissolving hyaluronic acid, its metal salt or a mixture thereof in water to form a solution; (2) Dispersion step: adding an alcohol substance to the above solution and stirring to form a dispersed mixed solution; (3) adding a cross-linking agent to the mixed solution and adjusting the pH to non-neutral; (4) cooling the mixed solution to between -15 and -50°C and performing a cross-linking reaction; (5) After the reaction is completed, optionally neutralize, purify and homogenize, The median of the pore size of the gel particles is equal to the median of the particle size of the gel particles D 50 The ratio is between 0.1-0.

5.

8. The method according to claim 7, wherein the alcohol substance is selected from monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1 to 26 carbon atoms, in particular, the alcohol substance is selected from monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1 to 16 carbon atoms, and even, the alcohol substance is selected from monohydric alcohols, dihydric alcohols or polyhydric alcohols having 1 to 8 carbon atoms, preferably, the alcohol substance is selected from methanol, ethanol, benzyl alcohol, ethylene glycol.

9. Use of the cross-linked hyaluronic acid gel particles according to any one of claims 1 to 6 in the preparation of medical cosmetic products, in particular in the preparation of products for the treatment of facial fine lines, facial sculpting, correction of facial features, surgery or surgical treatment, and even in the preparation of anti-adhesion and anti-scar products.

10. Use of the cross-linked hyaluronic acid gel particles according to any one of claims 1 to 6 in the preparation of products for soft tissue filling, wound hemostasis, wound healing, anti-scarring, scar repair, joint lubrication, and joint protection, especially in the dermis and subcutaneous tissue.